2015
DOI: 10.1189/jlb.4a1014-489r
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of miR-21 in the macrophage response to peritonitis

Abstract: We investigated the role of microRNA-21 in the macrophage response to peritonitis; microRNA-21 expression increases in peritoneal macrophages after lipopolysaccharide stimulation but is delayed until 48 hours after cecal ligation and puncture. MicroRNA-21-null mice and bone marrow-derived cell lines were exposed to cecal ligation and puncture or lipopolysaccharide, and survival, microRNA-21 levels, target messenger RNAs and proteins, and cytokines were assayed. Macrophages were also transfected with microRNA-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 60 publications
3
55
0
Order By: Relevance
“…MiR‐21 is ubiquitously expressed in multiple organs such as heart and kidney, which participates in the processes of inflammation process and organ malfunction associated with sepsis . For instance, overexpression of miR‐21 reduces TNF‐α level, while the inhibition of miR‐21 upregulates TNF‐α and IL‐6 levels .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiR‐21 is ubiquitously expressed in multiple organs such as heart and kidney, which participates in the processes of inflammation process and organ malfunction associated with sepsis . For instance, overexpression of miR‐21 reduces TNF‐α level, while the inhibition of miR‐21 upregulates TNF‐α and IL‐6 levels .…”
Section: Discussionmentioning
confidence: 99%
“…The present study disclosed that miR‐21 relative expression in sepsis patients was lower than that in HCs, and miR‐21 was with a good value for predicting reduced sepsis risk (AUC: 0.801, 95% CI: 0.758‐0.844). The possible explanations might be that: (a) MiR‐21 suppressed the release of macrophage cytokines (such as TNF‐α and IL‐6) via downregulating NF‐κB signaling, thus dampening inflammation and sepsis risk . (b) MiR‐21 might protect multiple organs (such as lung, kidney, and heart) from damage via reducing cell apoptosis and proinflammatory cytokines, thereby, alleviating organ injury and lowering sepsis risk …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al., who recently reported that the deficiency of miR-21 increases LPSinduced IL-6 formation via NF-B activation [244]. Further studies are required to examine the effect of NF-B inhibition on cytokine production in miR-21-KO macrophages.…”
Section: Mir-21 and Activation Of Caspases In Macrophagementioning
confidence: 97%
“…The role of miR-21 in LPS-induced inflammation has been a subject of intense investigation of late. Recently my mentor, in collaboration with others, showed that miR-21 protects from LPS-induced peritonitis [244]. However, the contribution of miR-21 in regulating TLR4 signaling in the context of atherosclerosis has not been examined.…”
Section: Introductionmentioning
confidence: 99%